Leadership matters unleashing the power of paradox - Cronin, Thomas E. (Boulder Paradigm Publishers, 2012)
Some leaders fundamentally alter the status quo whilst others guide quietly. Most leadership books emphasise specific rules, but Tom Cronin and Michael Genovese see leadership as filled with paradox. Leadership Matters offers a different view of leadership - one that builds community and responds creatively to new situations. Cronin and Genovese argue that leadership is about more than just charisma and set leaders on to a different path - to unleash the power of paradox.
Includes bibliographical references and index.
Keywords: Political leadership